IMPLEMENTATION OF SECURITY SYSTEMS FOR PREVENTION OF LOSS OF INFORMATION AT ORGANIZATIONS OF HIGHER EDUCATION - Boranbayev, Askar; Mazhitov, Mikhail; Kakhanov, Zhanat (The 12th International Conference on Information Technology: New Generations (ITNG 2015), 2015)
In this paper we discuss our experience of implementation of Data Loss Prevention (DLP) system at our University. The DLP system helps to analyze, control, monitor, block and protect data at the University. With the help of the DLP system and encryption we are able to protect and control the confidential data about our clients, HR data, intellectual ownership data, legal and financial documentation, official letter exchanges with partners and clients, academic and research data, etc...
Keywords: information security; data loss prevention; SOFTWARE; information system; data; Research Subject Categories::TECHNOLOGY